A standard for normalizing the outputs of triboelectric nanogenerators in various modes. Issue 9 (3rd August 2022) - Zhao, Da; Yu, Xin; Wang, Jianlong; Gao, Qi; Wang, Zhenjie; Cheng, Tinghai; Wang, Zhong Lin
Abstract : By the proposed standard of normalizing the output performance for triboelectric nanogenerators in various modes, it is proved that the order of influencing factors is contact area > film thickness > applied force > displacement distance. Abstract : A quantitative standard based on the internal equivalent circuit is proposed to evaluate the effects of different factors on the outputs of the triboelectric nanogenerators (TENGs) in various modes. This paper establishes the relationship between the equivalent circuits and TENGs, and then explores the influence of mechanical structures ( e.g. contact area and film thickness) and external excitations ( e.g. applied force, displacement distance, and triggering frequency) on output power and matching reactance by the normalization method. Moreover, the prototypes are fabricated to verify the rationality and feasibility of normalization. Experimental results show that the order of influencing factors is contact area > film thickness > applied force > displacement distance. The influence of frequency on the normal-directional moving TENG is greater than that on the tangential-directional moving TENG. This work provides a reference for quantifying the outputs of TENGs with different structures.